2011
DOI: 10.1111/j.1365-3148.2011.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of RBC transfusions on cytokine gene expression after cardiac surgery in patients developing post‐operative multiple organ failure

Abstract: When tested at 24 h after surgery, cytokine GE in peripheral blood leucocytes showed no significant differences between those transfused and those not transfused. Some alterations were seen in those developing MOF compared to those who did not, but the findings offer no role of leukocyte depleted (LD) RBC transfusion in the development of MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…This leads to multi-system and multi-cell activation and produces a large number of humoral and cellular inflammatory mediators through a cascade reaction, which eventually causes tissue and organ damage or even multiple organ dysfunction syndrome [8-10]. Causes of SIRS also include surgical injury, anesthesia, changes in body temperature, organ ischemia/reperfusion injury, machine blood transfusion, hemodilution, and heparin-protamine complexes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to multi-system and multi-cell activation and produces a large number of humoral and cellular inflammatory mediators through a cascade reaction, which eventually causes tissue and organ damage or even multiple organ dysfunction syndrome [8-10]. Causes of SIRS also include surgical injury, anesthesia, changes in body temperature, organ ischemia/reperfusion injury, machine blood transfusion, hemodilution, and heparin-protamine complexes [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the studies that found no effect, mixed effects, or immune‐suppressive effects associated with RBC transfusion largely employed leukoreduced RBC products . Immunosuppressive effects of transfusion have been studied most often in surgical patients .…”
Section: The Dynamic Immune Response To Critical Illnessmentioning
confidence: 99%
“…A few studies in the literature support this notion, [35][36][37] but others do not. [38][39][40] However, no data elements in the ACS-NSQIP database allow direct measurement of inflammatory mediators or molecular markers of inflammation that permit direct inference of the association between blood transfusion and surgical infections. Our results support a relationship between surgical infections and intraoperative blood transfusion and suggest the need for further efforts to investigate the effect of blood transfusion practices on surgical infections.…”
Section: Commentmentioning
confidence: 99%